Utilisation of cattle manure and inorganic fertiliser for food production in central Uganda - Muhereza, Innocent; Pritchard, Deborah; Murray-Prior, Roy (Istituto Agronomico per l'Oltremare di Firenze, 2014)
Cattle manure and inorganic fertiliser use in smallholder peri-urban crop-livestock farms in Uganda was investigated by conducting a survey of 40 farms in the central districts of Wakiso and Kampala. The results showed that the major benefits obtained from cattle manure application were increased yields (52.5 %) and low cost of manure purchase (37.5 %). The major problems associated with its use included weight and bulkiness (75 %), lack of labour (67.5 %), insufficient quantities (55 %), high transportation and application costs (37.5%), enhanced weed infestation (35 %), poor hygienic conditions (32.5 %) and lack of storage facilities to maintain quality attributes of manure (32.5 %). A large number of farmers supplemented the cattle manure with other animal manures, such as poultry (45 %), pig (38 %), goat (33 %) and rabbit (18 %) manures where available. The majority of farmers (95 %) never supplemented manure with inorganic fertiliser claiming that it was expensive in terms of purchase and transportation (90 %) and lack of capital to purchase the fertilisers (67.5 %). Farmers were aware of the benefits of using cattle manure as a source of fertiliser in their crop-livestock production system. However, the nutrient content of cattle manure was low (0.42-0.56 % total N), being attributed to poor handling, collection and storage of manure, insufficient fodder and poor livestock diet, which need better management to maximise nutrient recovery. There was little information available to farmers regarding optimum management and rates of fertiliser application (both inorganic and organic) to improve crop yields, which is required to improve food security and economic development in Uganda. Ugandan extension services should therefore make efforts to intensify education among farmers in relation to soil fertility management options. In addition, farmers should collect and store the manure properly and preferably in a covered pit to enhance manure quality. Effective manure handling and storage systems should be designed that reduce loss of nutrients after excretion and during composting. Farmers should explore the viability of community based manure collection initiatives at the farm level where manure transportation costs are shared and hence minimized.